Residual mechanical properties and spalling resistance of strain-hardening cementitious composite with Class C fly ash - Liu, Jin-Cheng (2020)
This study investigated fire resistance of strain-hardening cementitious composite (SHCC) incorporating Class C fly ash. The fly ash used is a local industrial byproduct. Adopting the local industrial byproduct would reduce the cost of SHCC significantly and reliance on overseas sources of fly ash. The results indicated that heat treatment up to 200 °C had negligible effect on strain capacity and strength of the SHCC specimens. Both compressive and tensile strengths began to deteriorate from 300 °C onwards. The SHCC specimens lost its strain-hardening feature at 300 °C and exhibited strain-softening behavior up to 600 °C. PVA fibers were found capable of increasing permeability of SHCC significantly before reaching melting point and reducing the risk of spalling under fire. This paper shows promising applications in introducing local industrial byproduct to produce green SHCC with excellent fire resistance.